Severe Actinomycotic Discitis Osteomyelitis and Bacteremia in an Immunocompetent Adult Following Dental Cleaning: A Case Report - Malik W. Z. Khan; Abdul Moeez; Sameen Farooq; Touba Azeem; Muhammad Ahmad; Aizaz Ali; Faheemullah Khan (Clinical Case Reports)
ABSTRACT Actinomycotic vertebral osteomyelitis is a rare but severe condition, even in immunocompetent individuals, following routine dental procedures. Prompt recognition, multidisciplinary management, and tailored antibiotic therapy are crucial for optimizing outcomes. Clinicians should maintain a high index of suspicion for Actinomyces in patients with unexplained spinal infections and recent dental interventions.